Predictors of foster parents’ stress and associations to sensitivity in the first year after placement - Gabler, Sandra; Kungl, Melanie; Bovenschen, Ina; Lang, Katrin; Zimmermann, Janin; Nowacki, Katja; Kliewer-Neumann, Josephine; Spangler, Gottfried (Child Abuse & Neglect, 2018)
In Germany, almost 70 000 children are living in foster families (Statistisches Bundesamt, 2016). Many foster children show mental health problems as they were exposed to an accumulation of risk factors. Hence, foster parents are often faced with challenging parenting situations. The current study focuses on the predictors of foster parents’ stress and examines longitudinally whether parenting stress is associated with foster parents’ sensitivity. The sample consisted of 55 children (aged from 1 to 6 years) and their foster caregivers. Foster parents’ sensitivity was observed during home visits. Caregiver reports were used to assess parenting stress (Parenting Stress Index) as well as foster children's externalizing behavior problems (Child Behavior Checklist). For main caregivers’ stress at the beginning of placement, regression analyses revealed both, foster children's externalizing problems as well as partners’ stress as predictive. For main caregivers’ stress one year after, only initial parenting stress and partners’ stress were predictive. Foster parents’ sensitivity was correlated with their parenting stress one year after placement. Regression analyses revealed no longitudinal effects of initial parenting stress on overall sensitivity. However, supportive presence was predicted by initial supportive presence and by the interaction between parenting stress and children's externalizing problems at placement. The findings highlight the role of the partner in experiencing parenting stress when taking care of a foster child. Furthermore, they emphasize that foster parents who care for children with behavior problems need adequate support that can buffer initial parenting stress and thereby promote sensitive caregiving.
Created from Fastlane, Scopus look-up
Keywords: Behavior problems; Foster children; Foster parents; Parenting stress; Sensitivity